Hubungan Motivasi dengan Produktivitas Pegawai di PT.Semadam Kabupaten Aceh Tamiang - Zainal, Zainal (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2019)
The most important thing in making the employed employees stay and contribute to the company is motivation. The management which is responsible on the matter of Human Resources usually conducts a series of particular attempts to give motovation to its employees. This research is conducted in P.T.Semadam Aceh Tamiang Regency to reveal the relation of motivation with productivity in P.T.Semadam.The respondents of this research are 50 with census sampling technique. The result of the research describes the employees in P.T.Semadam have some adequately high motivation and productivity. This matter is revealed by the disribution of the respondents’ answer to the biggest statement of motivation, that is agreeable 51,73%, very agreeable 20,4%, doubtful 15,87%, disagreeable 12%, and very disagreeable 0%. The disribution of the respondents’ answer to the biggest statement of productivity is agreeable 48,2%, very agreeable 27,6%, doubtful 16,8%, disagreeable 7,4%, and very disagreeable 0%. Based on this answer the relation between motivation and productivity of the employees in P.T.Semadam Aceh Tamiang Regency is influencing each other with its each value as many as 51,73% of motivaton and 48,2% of productivity.